Features pharmaceutical care to sick children in terms of implementation of health insurance - Bielyaieva, O. I.; Unhurian, L. M.; Pietkova, I. B. (Journal of Education, Health and Sport, 2016)
Children’s protection is of particular importance in the health system in Ukraine due to its significance for the development of society and interests of each family or a person. WHO determines that life, survival, maximum development, children’s access to health services is not only their basic needs but also basic human rights. The health of the children’s population is an indicator of social, economic and cultural development of any country in the world. In modern terms the situation observed in the development of children is a part of a demographic crisis, characterized by deterioration of not only quantitative but also qualitative characteristics of the population, including the growing problem of children’s health. In Ukraine, constant attention is paid to solving the most pressing problems related to maintaining the health of children in the process of reforming the health care system namely reducing child mortality rate, child morbidity and disability. These directions include the development of preventive measures, the construction of new structural health care units, national and regional epidemiological and clinical studies resulting in future tracing and monitoring the situation of the most urgent problems of pediatrics.